Diagnostik molekular thalassemia - Sunarto Sunarto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1996)
A diagnosis of thalassemias has advanced from clinical to molecular in concordance with the advances in molecular biology. Since the introduction of polymerase chain reaction procedure - a practical in vitro procedure of deoxyribonucleic acid amplification - various diagnostic methods have been developed, to detects either gene deletions or point mutations. In a population where the spectrum of mutations is not too heterogenous, direct methods such as dot blot or reverse dot blot hybridization, ligase chain reaction and amplification refractory mutation system may be applied with high effectivity dan efficiency. But, in a population where the spectrum of mutations is very heterogenous other methods such as mismatch analysis, denaturing gradient gel electrophoresis and single strand conformation analysis as the screening step followed by deoxyribonucleic acid sequencing are chosen. Each of the above methods has advantages and shortcomings, in relation to various problems among others the sensitivity, the specificity, the ease, the reproducibility and the cost.In this paper the molecular diagnostics, concerning the principle, the advantages and the shortcomings, espebially that have been used in the field are discussed.Key words: gene disorders - ligase chain reaction - dot blot and reverse dot blot hybridization - amplification refractory mutation system - denaturing gradient gel electrophoresis - single strand conformation analysis - chemical cleavage of mismatch